Making African Christianity : Africans re-imagining their faith in colonial southern Africa - Houle, Robert J., 1969- (Lehigh University Press ; Rowman & Littlefield, 2011)
In Making African Christianity author Robert J. Houle argues that Africans successfully naturalized Christianity. This book examines the long history of the faith among colonial Zulu Christians (known as amakholwa) in what would become South Africa. As it has become clear that Africans are not discarding Christianity, a number of scholars have taken up the challenge of understanding why this is the case and how we got to this point. Where others have focused on the economic and political potential of conversion, this book argues that we need to understand what was embedded within the faith that Africans found so appealing. Houle argues that translation did not end with the bible, but extended to Christian theology which needed to be fully appropriated before the faith was secure on the continent. . For Zulu, the religion was not a good fit until converts filled critical gaps in the faith, such as how Christianity could account for the active and everyday presence of the ancestral spirits- a problem that was true for African converts across the continent in slightly different ways. This book offers fresh insight into the history behind the contemporary success of Christianity on the continent and will be welcomed by African historians, thoseinterested in the history of colonialism, missions, southern African, and in particular Christianity.